Cobalt complexes based on hyperbranched salicylaldimine ligands as catalyst precursors for ethylene oligomerization. (24th February 2017) - Li, Cuiqin; Wang, Fengfeng; Lin, Zhiyu; Zhang, Na; Wang, Jun
Abstract : Three hyperbranched salicylaldimine ligands with tetradecyl as core, with hexadecyl as core and with octadecyl as core were synthesized in good yields. These ligands were reacted with cobalt chloride hexahydrate to form three complexes (C1 –C3 ). The compounds were characterized using Fourier transform infrared, 1 H NMR, mass and UV spectroscopies and thermogravimetric and differential thermal analyses. The catalytic properties of the hyperbranched cobalt complexes were evaluated for ethylene oligomerization. The effects of solvent and reaction parameters (Al/Co molar ratio, temperature and reaction pressure) on ethylene oligomerization were studied using the cobalt complex C3 as pre‐catalyst and methylaluminoxane (MAO) as co‐catalyst. Under these conditions ([Co] = 5 μmol, Al/Co = 500, 25 °C, 0.5 MPa ethylene, 30 min), the catalytic activity of complex C3 in toluene was 1.85 × 10 5  g (mol Co) −1  h −1 and the selectivity for C8+ oligomers was 55.72%. The complex structure also had a significant influence on both the catalytic activity and selectivity. All three cobalt complexes, activated with MAO, showed moderate activities towards ethylene oligomerization and the activity of cobalt complex C1 was up to 1.99 × 10 5  g (mol Co) −1  h −1 . The kinds of metal center of complexes (cobalt complex C1 and nickel complex with tetradecyl as core) and their catalytic properties were investigated in detail under the same conditions. Abstract : A series of novel hyperbranched salicylaldimine ligands and their cobalt complexes were synthesized and characterized. Upon activation with methylaluminoxane, all three cobalt complexes showed good to excellent activity towards ethylene oligomerization with activities up to 1.93 × 10 5  g (mol Co) −1  h −1 and selectivity for C8+ oligomers up to 55.72%.